2020
DOI: 10.3727/096504020x15907428281601
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironment Analysis of Prognosis and Molecular Signature of Immune-Related Genes in Lung Adenocarcinoma

Abstract: There is growing evidence on the clinical significance of Tumor Microenvironment (TME) cells in predicting prognosis and therapeutic effects. However, cell interactionsin tumor microenvironments have not been thoroughly studied or systematicallyanalyzed so far. In this study, 22 immune cell components in the lung adenocarcinoma(LUAD) TME were analyzed using gene expression profile from The Cancer GenomeAtlas (TCGA), Gene Expression Omnibus (GEO) . The TME based molecular subtypesof LUAD were defined to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…This suggests that the lower the amount of immune and stromal cells surrounding the tumor cells, the faster the tumor proliferates and progresses, and the worse the patient's prognosis may be. And this is relatively consistent with previous studies [20,21]. Figure 7: GSEA of TCGA cohort with oncogenic signature gene sets.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This suggests that the lower the amount of immune and stromal cells surrounding the tumor cells, the faster the tumor proliferates and progresses, and the worse the patient's prognosis may be. And this is relatively consistent with previous studies [20,21]. Figure 7: GSEA of TCGA cohort with oncogenic signature gene sets.…”
Section: Discussionsupporting
confidence: 90%
“…Patients who can benefit from targeted therapy or immunotherapy have more prolonged survival and higher quality of life than those on regular chemotherapy, based on gene mutations and immunohistochemistry. According to previous studies, an excellent prognostic marker or model helps in predicting patient survival and better clinical management [20,21]. Recently, Ling et al used differentially expressed genes closely related to the tumor microenvironment to construct models to predict patient prognosis and explore the relationship between patient responsiveness to immunotherapy and the tumor microenvironment [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding TME and recognizing genes related to TME can provide new ideas for immunotherapy. In the TME, many cancer cells and immune cells mediate signaling pathways ( Marwitz et al, 2021 ), involving in tumor progression and drug resistance ( Santaniello et al, 2019 ; Ling et al, 2020 ). In view of the low treatment rate of LUAD patients with high pathogenicity, it is imperative to find new gene markers ( Zhou C. S. et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence indicates that the tumor microenvironment (TME) has significant clinical value in predicting prognosis ( Pu et al, 2019 ; Hong et al, 2020 ; Ling et al, 2020 ; Qu et al, 2020 ). Previous studies indicated that T cells were positively correlated with good clinical outcomes in OC ( Fridman et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%